Diagnosis and management of iatrogenic endoscopic perforations: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement – Update 2020 - Paspatis, Gregorios A.; Arvanitakis, Marianna; Dumonceau, Jean-Marc; Barthet, Marc; Saunders, Brian; Turino, Stine Ydegaard; Dhillon, Angad; Fragaki, Maria; Gonzalez, Jean-Michel; Repici, Alessandro; van Wanrooij, Roy L.J.; van Hooft, Jeanin E. (Endoscopy, 2020)
1 ESGE recommends that each center implements a written policy regarding the management of iatrogenic perforations, including the definition of procedures that carry a higher risk of this complication. This policy should be shared with the radiologists and surgeons at each center.2 ESGE recommends that in the case of an endoscopically identified perforation, the endoscopist reports its size and location, with an image, and statement of the endoscopic treatment that has been applied.3 ESGE recommends that symptoms or signs suggestive of iatrogenic perforation after an endoscopic procedure should be rapidly and carefully evaluated and documented with a computed tomography (CT) scan.4 ESGE recommends that endoscopic closure should be considered depending on the type of the iatrogenic perforation, its size, and the endoscopist expertise available at the center. Switch to carbon dioxide (CO2) endoscopic insufflation, diversion of digestive luminal content, and decompression of tension pneumoperitoneum or pneumothorax should also be performed.5 ESGE recommends that after endoscopic closure of an iatrogenic perforation, further management should be based on the estimated success of the endoscopic closure and on the general clinical condition of the patient. In the case of no or failed endoscopic closure of an iatrogenic perforation, and in patients whose clinical condition is deteriorating, hospitalization and surgical consultation are recommended.